Speed Sensorless Direct Rotor Field-Oriented Control of Single-Phase Induction Motor Using Extended Kalman Filter - Mohammad Jannati; Seyed Hesam Asgari; Nik Rumzi Nik Idris; Mohd Junaidi Abdul Aziz (Institute of Advanced Engineering and Science, 2014)
Nowadays, Field-Oriented Control (FOC) strategies broadly used as a vector based controller for Single-Phase Induction Motors (SPIMs). This paper is focused on Direct Rotor FOC (DRFOC) of SPIM. In the proposed technique, transformation matrices are applied in order to control the motor by converting the unbalanced SPIM equations to the balanced equations (in this paper the SPIM with two different stator windings is considered). Besides this control technique, a method for speed estimation of SPIM based on Extended Kalman Filter (EKF) to achieve the higher performance of SPIM drive system is presented. Simulation results are provided to demonstrate the high performance of the presented techniques.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6098